Heat transfer enhancement of Cu-water nanofluid in an inclined porous cavity with internal heat generation. (December 2017) - Rajarathinam, M.; Nithyadevi, N.
Highlights: Convection of nanofluid saturated porous medium is studied. Darcy-Brinkman-Forchheimer model is adopted in the present study. Their results show that the effect of solid volume fraction is affected by strong heat generation parameter. The inclination angle 90° affects the augmented heat transfer rate. Abstract: In this paper, the effect of internal heat generation on an unsteady laminar convection in a porous cavity filled with a Cu-water nanofluid has been reported numerically. Horizontal walls of the cavity are thermally insulated and different constant temperatures are imposed at the vertical walls. The transport equations for nanofluid saturated porous medium has been modeled by Darcy-Brinkman-Forchheimer equations and are solved by using SIMPLE algorithm. The influence of various non-dimensional parameters such as internal heat generation Q, inclination angle γ, Darcy number Da and solid volume fraction ϕ have been analyzed. The obtained results reveals that the utilization of nanofluid is insignificant at the presence of strong internal heat generation.